Transcriptomic analysis of sweet potato under dehydration stress identifies candidate genes for drought tolerance - Lau, K.H.; Herrera, M.R.; Crisovan, E.; Wu, S.; Muhammad, Z.F.; Khan, A.; Buell, C.R.; Gemenet, D. (Wiley, 2018)
Sweet potato (Ipomoea batatas [L.] Lam.) is an important subsistence crop in Sub‐Saharan Africa, yet as for many crops, yield can be severely impacted by drought stress. Understanding the genetic mechanisms that control drought tolerance can facilitate the development of drought‐tolerant sweet potato cultivars. Here, we report an expression profiling study using the US‐bred cultivar, Beauregard, and a Ugandan landrace, Tanzania, treated with polyethylene glycol (PEG) to simulate drought and sampled at 24 and 48 hr after stress. At each time‐point, between 4,000 to 6,000 genes in leaf tissue were differentially expressed in each cultivar. Approximately half of these differentially expressed genes were common between the two cultivars and were enriched for Gene Ontology terms associated with drought response. Three hundred orthologs of drought tolerance genes reported in model species were identified in the Ipomoea trifida reference genome, of which 122 were differentially expressed under at least one experimental condition, constituting a list of drought tolerance candidate genes. A subset of genes was differentially regulated between Beauregard and Tanzania, representing genotype‐specific responses to drought stress. The data analyzed and reported here provide a resource for geneticists and breeders toward identifying and utilizing drought tolerance genes in sweet potato.